PWE-188 Using a "conversion factor" to estimate adenoma detection rate. (28th May 2012) - Rajasekhar, P T; Lee, T J; Rutter, M D; Bramble, M G; Wilson, D W; East, J E; Saunders, B P; Hungin, P; Rees, C J
Abstract : Introduction: Adenoma detection rate (ADR) is the recommended surrogate marker for a thorough colonoscopic examination. Collecting histology makes its calculation arduous so polyp detection rate (PDR) is often used instead. It has been proposed that the ADR:PDR ratio can be used as a "conversion factor" to accurately estimate ADR. Work from the Bowel Cancer Screening Programme (BCSP) has shown that adenomas are more prevalent in this population suggesting the ratio may be different. We aimed to assess the feasibility of using a "conversion factor" to estimate ADR from PDR in different UK populations. Methods: Colonoscopy performance data from the symptomatic services were collected over a 3-month period from 12 units in the northern region of England. Data from all procedures performed by BCSP accredited colonoscopists were excluded from this group. National colonoscopy performance data were extracted from the BCSP database from a 12-month period. Colonoscopists detecting polyps in ≥10 patients were included. Data collected included colonoscopist, PDR and ADR. The conversion factor was calculated separately for each group. The ADR:PDR ratio was calculated at the level of the colonoscopist and the group mean used as the conversion factor. The estimated ADR was calculated using: PDR × conversion factor. The relationship between the actual and estimated ADR was evaluated using Pearson's correlation coefficient. Results: In the symptomatic services 3219 colonoscopies were performed by 55 colonoscopists. In the BCSP 31 017 procedures were performed by 147 colonoscopists. The PDR and ADR respectively for the symptomatic group were 30.7%, IQR 24.8–40.0 and 18.0%, IQR 14.0–24.0, and for the BCSP group were 59.3%, IQR 53.8–65.0 and 46.0%, IQR 43.0–51.3. The ADR:PDR ratio in the symptomatic and BCSP groups were 0.59 (IQR 0.47–0.69) and 0.78 (IQR 0.74–0.81). The correlation between the estimated and actual ADR was 0.68 (p<0.001) and 0.83 (p<0.001) for the symptomatic and BCSP groups respectively. Conclusion: We demonstrate using estimated ADR, when calculation of ADR is not feasible, may be an acceptable marker of quality in colonoscopy. The difference in the conversion factors between the groups studied here is likely to be due to the selected population colonoscoped within the BCSP but suggests it will need to be adjusted for different patient populations. Studies to further validate this concept and ensure that conversion factors remain consistent over time are ongoing. Competing interests: None declared.